SOME CURRENT ISSUES IN MODERN FORENSIC PRACTICE - Nikolai N. Il'in (Теория и практика судебной экспертизы, 2018)
The paper looks at some issues with how forensic examinations are classified, commissioned and conducted. Analysis of scientific literature reveals that the diversity of new and emerging forensic science disciplines puts the questions of their classification at odds with current practice. The author highlights some of these contradictions and offers solutions to issues arising in the process of commissioning and conducting forensic nonconventional examinations.